EVALUASI KINERJA ASET DI INDONESIA BERDASARKAN RISK-ADJUSTED : STUDI KOMPARATIF MENGGUNAKAN INDEKS SHARPE, TREYNOR, DAN ALPHA JENSEN - Azmi, Muhammad Syaufi; Redawati, Redawati; Asma, Rusdayanti; Supriyanto, Akhmad; Stiadi, Doni (Servqual: Jurnal Ilmu Manajemen, 2025)
This study evaluates and compares the performance of alternative and traditional investment assets in Indonesia using a risk-adjusted approach. The growing interest in non-traditional assets, such as Bitcoin, alongside traditional assets like stocks (LQ45 Index) and gold, underscores the need to assess their comparative efficiency under the same financial evaluation metrics. The primary objective of this research is to analyze which of these three assets offers the most optimal return relative to the risk undertaken by investors during the observation period. Using secondary data for the period January to December 2021, this study employs three key risk-adjusted performance measurement tools: the Sharpe Index, Treynor Index, and Jensen's Alpha. The results show significant variation in risk-adjusted performance across asset classes. Bitcoin demonstrates the highest return potential but also carries the greatest risk and volatility. The LQ45 Index offers a more stable and moderate performance, while gold provides a conservative investment profile with relatively consistent returns. Overall, the Treynor and Sharpe ratios place Bitcoin at the top in terms of return-to-risk efficiency, while the Jensen’s Alpha presents a more nuanced view depending on market conditions and benchmark selection. These findings provide valuable insights for investors in constructing diversified portfolios and assessing asset choices under different market conditions. This study contributes to the literature by offering a comparative lens on traditional versus alternative assets within the Indonesian financial context using standardized performance metrics.